(Effect of Banana Type, Amount and Duration Concentrate Storage Quality Against Soft Drinks Fruit Banana) - Indra Neffi Ridwan; Eppy Susanto; F.G. Winarno (Balai Besar Industri Agro, 1987)
The research was aimed at studying the effect of banana variety, amount of concentrate and lenght of storage on the quality of soft drink made of banana juice. The result showed that banana of